Work incentives across the income distribution and for model families in Lithuania: 2005–2013. Issue 2 (2nd July 2016) - Navickė, Jekaterina; Lazutka, Romas
ABSTRACT: The aim of this paper is to evaluate the impact of cash social benefits on work incentives across the income distribution and among selected model family types in Lithuania. The analysis of work incentives was carried out for 2005–2013 based on a combination of measures estimated using the EUROMOD tax–benefit microsimulation model. The analysis revealed high disincentives to work at the bottom of the income distribution, dominated by the effect of cash social benefits compared to taxes or social insurance contributions. A strong trade-off between benefit adequacy and work incentives is built into the design of the national cash benefit system, particularly social assistance. The challenge for policy design is thus to encourage active labour market participation among low earners without eroding the minimum income protection floor.